Assessing the Feasibility of Downsizing Municipalities in Saudi Arabia: A Path Toward Efficiency - Alhowaish, Abdulkarim K. (Journal of Cultural Analysis and Social Change, 2025)
This study investigates the feasibility and implications of municipal downsizing, defined as the structural consolidation or amalgamation of small or overlapping municipalities rather than internal administrative retrenchment, within the Kingdom of Saudi Arabia. The research focuses on improving governance efficiency, service delivery, and institutional coordination. Against the backdrop of Saudi Vision 2030 and ongoing decentralization efforts, three questions are addressed: (1) Can municipal consolidation enhance local governance efficiency? (2) What structural, cultural, and economic barriers impede such reform? (3) How can restructuring balance fiscal efficiency with the preservation of local identity? A mixed-methods design was adopted, not solely for triangulation but to achieve complementarity and development between quantitative and qualitative strands. Quantitative survey data from 375 stakeholders, policymakers, municipal employees, civic-minded citizens, and governance experts, were integrated with qualitative thematic analysis. The findings reveal moderate but differentiated support for downsizing, with variables such as age, education, and stakeholder role influencing perceptions. Regression and ANOVA results show statistically significant divergences, particularly concerning expected cost savings and perceived impacts on service quality. A contextual case analysis of the Eastern Province, where selected municipalities were recently merged, further illustrates mixed satisfaction with previous consolidations, underscoring concerns about rural marginalization and administrative overreach. Digital transformation, public-service enhancement, and strengthened inter-municipal coordination emerged as the preferred reform priorities. Yet apprehensions remain regarding representation, identity erosion, and uneven development. The results emphasize the need for a phased, inclusive, and adaptive reform strategy that aligns with local sociocultural contexts and is anchored in measurable performance outcomes. By bridging local insights with global experiences, this study contributes to the wider literature on public-sector restructuring and offers actionable pathways for Saudi policymakers navigating the complexities of territorial reform in a highly centralized administrative system pursuing Vision 2030’s governance-transformation goals